Тунелепрохідницький щит з формуючим ротором - Свєшніков, І.А.; Шевчук, С.П.; Гарнець, В.М.; Зайченко, С.В.; Матвєєв, О.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The article considers the of processes of creation of tunnel machines of TBM type. The offered chart of a tunnel building allows to increase the operation speed. Co-operation with the developed soil is considered to determine the productivity of forming process.